Sectors Using, Necessarity and Benefits of Green Technologies - Sodikjon Saidjonovich Mukhlisov (Indonesian Journal of Innovation Studies, 2022)
This article discusses about the Green technologies, sectors using green technologies and the benefits of green technology and the obstacles to overcome